Upper extremity musculoskeletal discomfort among occupational notebook personal computer users: Work interference, associations with risk factors and the use of notebook computer stand and docking station. - Nunes, Isabel L.; Erdinc, Oguzhan (Work, 2011)
Objective: This study explored the prevalence and work interference (WI) of upper extremity musculoskeletal discomfort (UEMSD) and investigated the associations of individual and work-related risk factors and using a notebook stand or docking station with UEMSD among symptomatic occupational notebook personal computer (PC) users. Participants: The participant group included 45 Turkish occupational notebook PC users. Methods: The study used self-reports of participants. The Turkish version of the Cornell Musculoskeletal Discomfort Questionnaire (T-CMDQ) was used to collect symptom data. Results: UEMSD prevailed mostly in the neck, the upper back, and the lower back with prevalence rates of 77.8%, 73.3%, and 60.0% respectively, and with WI rates of 28.9%, 24.4%, and 26.7% respectively. Aggregated results showed that 44% of participants reported WI due to UEMSD in at least one body region. Significant risk factors were: being female, being aged < 31 years, having computer work experience <10 years, and physical discomfort during computer use. Conclusions: UEMSD prevalence and WI rates were considerable in the neck, the upper back, and the lower back. Significant associations between certain risk factors and UEMSD were identified, but no association was found between using notebook stand and docking station and UEMSD among participants.